A novel biobased intumescent flame retardant through combining simultaneously char-promoter and radical-scavenger for the application in epoxy resin. (February 2022) - Yang, Yunxian; Li, Zhi; Wu, Guang; Chen, Wen; Huang, Guangyan
Highlights: A biobased intumescent flame retardant (PAD) with different oxidation state of P was synthesized PAD functioned in both condensed and gas phases due to special chemical structure Epoxy with PAD and DOT exhibited excellent fire retardancy due to the synergistic effect A promising way to achieve eco-friendliness and high-efficiency was proposed Abstract: A biobased intumescent flame retardant (PAD) with different oxidation state of phosphorus was synthesized successfully via combining phytic acid (PA) and 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO). The chemical structure and performance of PAD were characterized by FTIR, 1 H NMR, 31 P NMR, and TGA, respectively. After introducing 5wt% PAD into epoxy resin, the EP samples exhibited expansive behavior during combustion and left char residue with 14.4% mass and 2.4 cm height. Meanwhile, the combination of 5wt% mixture of PAD and a borate (DOT) demonstrated good synergistic effect and further improved the flame retardancy of EP sample, as reflected by increased LOI value of 29%, V-0 rating in UL-94 test and char residue of 15.4%. Compared with neat EP sample, the PHRR and FIGRA reduced by 42.8% and 42%, respectively. Moreover, the initial decomposition temperature (T5wt% ) also increased to 350 °C. Finally, SEM/EDS, Raman, TG-IR, and Py-GC/MS were employed to evaluate the flame-retardant mechanism. This novel intumescent flame retardant PAD functioned in both condensed and gas phases, and the synergistic effect of PAD and DOT brings out excellent flame retardancy for epoxy.